The Influence of Fatherless on Marriage Motivation Girls in Situbondo District - Janatul Firdaus, Laili; Kumaini, Ruston (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
AbstractThe phenomenon of fatherlessness is a significant social issue in Indonesia, with 20.9% of children growing up without the presence of a father. This study aims to explore the factors contributing to the fatherless phenomenon and investigate its impact on the marriage aspirations of girls in the Situbondo District. The research adopts a qualitative approach with a case study design. The findings reveal four main factors causing fatherlessness: lack of support during the developmental years, parental divorce, paternal neglect, and emotional absence. These factors contribute to low self-confidence and uncertainty in forming relationships. Some informants expressed a positive desire to marry, although past trauma made them more selective in choosing a partner. Others, however, felt doubtful or skeptical about marriage due to past experiences. It can be concluded that the fatherless experience has diverse influences on the motivations and desires for marriage among girls. These differences include coping strategies for trauma and varying criteria for choosing a partner. However, a common thread among them is the awareness of the importance of a responsible male figure and the need for emotional security and stability. This study emphasizes that father involvement is crucial in the psychological development and relational dynamics of girls and provides important insights for parents and policymakers to design more effective interventions to support children in similar situations. Furthermore, it highlights the need for greater attention to the fatherless issue within communities, particularly in Situbondo District.